Leadership and Organizational Culture in Higher Education Institutions: Development Approaches Towards Excellence in the Era of Change - Suksai, Suktip; Pholpuntin, Sirote; Chaleysub, Sukhum; Chancharoen, Pitauk (Suan Dusit Graduate School Academic Journal, 2025)
This study aimed to analyze the roles and interrelationships between leadership and organizational culture in higher education institutions, with a particular focus on Thai higher education in the context of rapid change. Employing a comprehensive literature review and case study analysis of both domestic and international institutions, the research revealed that effective leadership in modern higher education should integrate characteristics of transformational, digital, and ethical leadership, coupled with adaptability and strategic thinking. Concurrently, organizational culture should emphasize learning, innovation, flexibility, collaboration, and social responsibility. The study advocated for a systematic and concurrent development of both leadership and organizational culture, taking into account the unique context of each institution and the challenges posed by an Era of Change. This article presented strategies for enhancing leadership and organizational culture in Thai higher education institutions, aimed at elevating educational quality, fostering innovation, and bolstering international competitiveness. Furthermore, it proposed avenues for future research to expand the knowledge base in this critical area.